2013
DOI: 10.1103/physreve.87.042805
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of emotions on networks leads to the evolution of cooperation in social dilemmas

Abstract: We show that the resolution of social dilemmas in random graphs and scale-free networks is facilitated by imitating not the strategy of better-performing players but, rather, their emotions. We assume sympathy and envy to be the two emotions that determine the strategy of each player in any given interaction, and we define them as the probabilities of cooperating with players having a lower and a higher payoff, respectively. Starting with a population where all possible combinations of the two emotions are ava… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(51 citation statements)
references
References 55 publications
(73 reference statements)
2
48
1
Order By: Relevance
“…By using a genetic algorithm we have studied the evolutionary process of these quantities within the framework of Prisoner's Dilemma game. As this finding is different from the results in (Szolnoki et al 2011(Szolnoki et al , 2013, we have demonstrated that the emotional diversity of individuals can evolve to a state where diversity is maintained. Furthermore, this emotional diversity of individuals can result in the boost of cooperation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…By using a genetic algorithm we have studied the evolutionary process of these quantities within the framework of Prisoner's Dilemma game. As this finding is different from the results in (Szolnoki et al 2011(Szolnoki et al , 2013, we have demonstrated that the emotional diversity of individuals can evolve to a state where diversity is maintained. Furthermore, this emotional diversity of individuals can result in the boost of cooperation.…”
Section: Discussioncontrasting
confidence: 99%
“…In Section 2, we introduce the applied microscopic model and discuss some consequences of emotional diversity. The difference between references (Szolnoki et al, 2011;Szolnoki et al, 2013) and this study is that the emotional model in (Szolnoki et al 2011(Szolnoki et al , 2013 has two parameters (α, β), whereas we establish an emotional model with four parameters {W , D, α, β}, where two types of compassion and harshness attitude to a weaker one and two types of respect and envy attitude to a stronger one are considered. Our results are presented in Section 3, and in Section 4 we summarise the results and outline some biological implications of our findings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing interest in using mathematics and computational methods in psychology [1][2][3][4][5][6][7][8][9][10]. Some mathematicians and psychologists have introduced mathematical models for romantic relationships [3,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…When a delay time is comparable to or larger than characteristic time scales, the time delay brings about rich phenomena. It leads to multistable synchronized states for phase oscillators [1][2][3][4][5][6][7], amplitude death for coupled limitcycle oscillators [8,9], stabilization of periodic orbits in chaotic systems [10], a resonant behavior in stochastic systems [11][12][13], dynamic instability in feedback control systems [14], a pattern formation in evolutionary game dynamics [15,16], and so on.In this Letter, we investigate the effects of time delay on the ordering dynamics in the context of the voter model (VM). The VM is a prototypical model for opinion dynamics [17][18][19][20][21][22].…”
mentioning
confidence: 99%